Mutational Profile in Vulvar, Vaginal, and Urethral Melanomas: Review of 37 Cases With Focus on Primary Tumor Site. (November 2020) - Zarei, Shabnam; Voss, Jesse S.; Jin, Long; Jenkins, Sarah M.; Bryce, Alan H.; Erickson, Lori A.; Bell, Debra A.; Kipp, Benjamin R.; Flotte, Thomas J.
Abstract : Melanomas of female genital tract are rare tumors with poor prognosis. While BRAF-V600E is the most common pathogenic mutation seen in cutaneous sun-exposed melanomas, mucosal and anogenital melanomas usually lack BRAF mutations and instead they harbor KIT alterations. The American Joint Committee on Cancer staging guideline (AJCC eighth edition) recommends using cutaneous melanoma guidelines for vulvar melanoma staging and does not provide any recommendations for vaginal melanoma staging. The aim of this study is to investigate the mutational status of invasive melanomas arising from different anatomic sites in lower female genital tract (vulvar hair-bearing skin, glabrous skin, vagina and urethra) in a group of 37 patients. Tumors were analyzed using a DNA targeted next-generation sequencing panel covering the 21 most common genes and mutation hotspots in melanomas. The most common genetic alterations in invasive melanomas of lower female genital tract are KIT (32%), TP53 (22%), and NF1 (19%). Overall 66% (21/32) of cases showed a pathogenic alteration in at least one of the MAPK pathway genes. No statistical significance seen between different primary tumor sites and the frequency of the oncogenic mutations, nor were any significant differences found by mutation status. Only one case of urethral melanoma showed a BRAF non- V600E mutation (D594G). Our results suggest a similar molecular pathogenesis and overall survival in melanomas arising from lower female genital tract, irrespective of their exact location in the urogenital area. Future classifications of melanoma should consider grouping vulvar melanomas with mucosal rather than cutaneous melanomas.